MTX intolerance in children and adolescents with juvenile idiopathic arthritis. (7th April 2020) - Hügle, Boris; van Dijkhuizen, E H Pieter
Abstract: MTX is the medication most commonly used for antirheumatic treatment in juvenile idiopathic arthritis. It has high efficacy, is usually well tolerated and has an excellent safety profile. However, frequently intolerance symptoms develop that manifest as nausea, feelings of disgust or abdominal complaints prior to or directly after administration of the medication. No obvious toxicity is causing these intolerance symptoms, but symptoms are strictly limited to MTX and not transferred to other medications. MTX intolerance causes a significant reduction of quality of life in affected patients, frequently puts the treating physician in difficult situations regarding treatment choice, and may lead to uncomfortable decisions whether or not to stop an otherwise effective drug. Conventional countermeasures such as antiemetics, change of route from subcutaneous to oral or vice versa, or taste masking usually have only a limited effect. In this review, we present the current knowledge on MTX intolerance, its clinical picture and commonly employed strategies. We also consider newer behavioural treatment strategies that may offer a more effective symptom control.